Predictors for incomplete response to ursodeoxycholic acid in primary biliary cholangitis. Data from a national registry of liver disease. Issue 6 (8th June 2021) - Cortez‐Pinto, Helena; Liberal, Rodrigo; Lopes, Susana; Machado, Mariana V.; Carvalho, Joana; Dias, Teresa; Santos, Arsénio; Agostinho, Cláudia; Figueiredo, Pedro; Loureiro, Rafaela; Martins, Alexandra; Alexandrino, Gonçalo; et al.
Abstract: Background: The current standard of treatment in primary biliary cholangitis (PBC) is ursodeoxycholic acid (UDCA), although a considerable proportion of patients show incomplete response resulting in disease progression. Objective: This study aimed to assess the prevalence of incomplete response to UDCA and determine associated patients' characteristics. Methods: Patients with PBC as main diagnosis were included from a national multicentric patient registry—Liver.pt. Main endpoints included incomplete response to UDCA treatment according to Barcelona, Paris I and Paris II criteria, Globe and UK PBC scores and the association between baseline characteristics and incomplete response according to Paris II criteria. Results: A total of 434 PBC patients were identified, with a mean age of 55 years and 89.2% females. Nearly half of patients were asymptomatic at diagnosis and 93.2% had positive anti‐mitochondrial antibodies. Almost all patients (95.6%) had been prescribed at least one drug for PBC treatment. At the last follow‐up visit, 93.3% were under treatment of which 99.8% received UDCA. Incomplete response to UDCA was observed in 30.7%, 35.3%, 53.7% and 36.4% of patients according to Barcelona, Paris I, Paris II criteria and Globe score, respectively. After adjusting for age and sex, and accordingly to Paris II criteria, the risk for incomplete biochemical response was 25% higher for patients with cirrhosis at diagnosis (odds ratio [OR] = 1.25; 95% confidence interval [95%CI]: 1.02–1.54; p = 0.033) and 35% (95%CI:1.06–1.72; p = 0.016) and 5% (OR = 1.05; 95%CI:1.01–1.10; p = 0.013) for those with elevated gamma‐glutamyl transferase (GGT) and alkaline phosphatase (ALP). Conclusion: A considerable proportion of patients showed incomplete biochemical response to UDCA treatment according to Paris II criteria. Cirrhosis, elevated GGT and ALP at diagnosis were identified as associated risk factors for incomplete response. Early identification of patients at risk of incomplete response could improve treatment care and guide clinical decision to a more careful patient monitorization. Abstract :